Dispersal and competitive release affect the management of native and invasive tephritid fruit flies in large and smallholder farms in Ethiopia - Biasazin, Tibebe Dejene (Sci Rep, 2021)
African horticulture is seriously affected by fruit flies, both native and invasive. Novel sustainable control methods need testing against the backdrop of smallholder-dominated farming of Africa. We evaluated the potential of male-specific attractants (parapheromones) laced with insecticide to suppress the alien invasive Bactrocera dorsalis and native Ceratitis capitata. In large-scale guava, methyl-eugenol (ME)-bait stations combined with toxic protein baits suppressed B. dorsalis within 8 months but resulted in a resurgence of the displaced Ceratitis capitata. In smallholder farms, intervention using SPLAT-ME laced with spinosad was surprisingly unsuccessful. Subsequent mark-release-recapture experiments showed high dispersal rates of flies, covering many times a typical farm size, leading to a continuous influx of flies from surrounding areas. Several other factors important for intervention were evaluated. SPLAT-MAT-ME dollops remained attractive for over two weeks, although gradually becoming less attractive than fresh baits. Further, competitive displacement was observed: C. capitata selectively emerged from fruits in which B. dorsalis infestation was low. Finally, we evaluated whether ME could be combined with C. capitata male attractants [trimedlure (TML) and terpinyl acetate (TA)] without affecting attraction. Combining male lures did not affect catches directly, although at very high populations of B. dorsalis attracted to ME interfered with C. capitata trap entry. Although ME-based methods can effectively suppress B. dorsalis, they were not effective at single smallholder scale due to the high dispersive propensity of tephritids. Further, competitive release implies the need for a combination of lures and methods. These observations are important for developing control schemes tailored for African smallholder settings.